Navigating Supply Chain Shortages in the Transition to Sustainable Transportation: The Role of Critical Materials Beyond Batteries - Diana Artudean; Norbert Kertész; Dan-Cristian Popa; Laura Bacali; Loránd Szabó (Engineering Proceedings)
This paper examines the crucial role of critical materials in sustainable transportation, specifically focusing on electric machines, power electronics, and lightweight materials, while deliberately omitting batteries from the analysis. It addresses the challenges arising from supply chain shortages and presents solutions through legislative, economic, and technological measures. Ensuring a stable supply of these materials is crucial for supporting the transition to greener and more efficient future transportation.